Describing Polygonum aviculare emergence in different tillage systems. (15th April 2015) - Royo‐Esnal, A; García, A L; Torra, J; Forcella, F; Recasens, J; Liebman, Matt
Summary Effects of four tillage systems (direct drill, subsoiler, chisel plough and mouldboard plough) on the dynamics of Polygonum aviculare populations were studied over three growing seasons. Cumulative emergence on a weekly basis was determined. Cumulative emergence from two years of chisel ploughing was used to develop an emergence model for P. aviculare based on hydrothermal time. Results showed that direct drilling, which had the highest seed yields of winter cereal crops every season, was the unique soil management system that lowered P. aviculare populations because of effective weed emergence reduction. The model accurately described seedling emergence in different tillage systems, although it failed in direct drilling, probably due to very low numbers of emerged seedlings. To better control this weed, direct drilling may be the best tillage option, but if this cannot be implemented, the hydrothermal time model is a practical tool that can describe the relative proportions of emergence and assist in the timing for management operations of P. aviculare in different tillage systems.